Integrated islamic education in Brunei Darussalam: philosophical issues and challenges - Maimun Aqsha Lubis,; Ramlee Mustapha,; Abdullah Awang Lampoh, (2009)
The purpose of this study was to examine the implementation of Integrated Islamic Education in Brunei Darussalam. The establishment of Pioneer Schools (Sekolah Rintis) in integrated Islamic education in 2003-2004 are solid evidence that Brunei has decided to settle on the Integrated Education for its future generations. However, some problems surface later, which are thought to impede the implementation of the Integrated Islamic Education in the country. This article aims to examine the extent of the implementation of the Integrated Islamic Education system in Brunei Darussalam and to evaluate whether there is an evident needed to revise the current system. The study found that even though the concept of Integrated Islamic Education is well-received by the society, the teachers are ill-equipped with the effective strategies to inculcate the spirit of the Integrated Islamic Education in their classrooms.